African meteorological institutions provide new high-resolution seasonal climate analyses for agricultural decision-making across 5 countries and regionally - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Five National Meteorological Services serving a rural population of 125 million, and two regional climate centers, in Africa routinely provide new high-resolution information and analyses of growing season characteristics for agricultural and food security decision-makers. The process has elevated the capacity and status of collaborating NMS. CCAFS developed the new tools, and contributed to their implementation and capacity development in partnership with the IRI's ENACTS (Enhancing National Climate Services) initiative.